A generalized hybrid model considering earthquake-induced internal force distribution rules for super high-rise frame-core tube structures. (1st October 2022) - Lai, Xiao; He, Zheng
Highlights: A generalized hybrid model (GHM) to estimate the distribution of shear forces and overturning moments is proposed. The GHM integrates the features of the flexure-shear coupled model and modified rocking model. The rotational stiffness matrix considers the constraint of the frame on the rotations of outriggers. Four indexes to calibrate parameters of the GHM are proposed. The effectiveness and accuracy of the GHM are demonstrated by the case study. Abstract: To efficiently control of the stiffnesses of the two sub-systems, i.e., the frame part and core tube part, of the frame core-tube structure commonly-used in super high-rise buildings, via the distributions of story shear force ratio and overturning moment ratio, as well as elastic inter-story drift ratio, a generalized hybrid model (GHM) is developed in which the feature of the flexure-shear coupled model (FSM) and the modified rocking model (SSM) has been integrated. It can be transformed into the FSM and SSM in some specific cases. The dynamic properties of the GHM are obtained in a semi-analytical way with the assistance of the analytical solution for the free vibration of the FSM and the analytically generated rotational stiffness matrix using the force method. To calibrate the four parameters, η, μ, α and ( EI T )0, associated with the GHM, the corresponding stiffness-based calibration indexes of T 1, T 2 / T 1, R V-1 and R M-1 are selected. The trust-regional-dogleg algorithm is adopted to solve the nonlinear equations consisting of the model parameters and targeted indexes. The effectiveness and applicability of the GHM are demonstrated from the case study on a series of finite element models with different parameters, from the aspects of the distributions of the inter-story drift ratios, the story shear force ratios and overturning moment ratios, as well as the vibration periods and modal mass participation coefficients. The two distribution ratios are observed to be controlled efficiently by adjusting the ratios of the shear stiffness of the frame and the axial stiffness of the frame column to the flexural stiffness of the core tube, respectively.